(untitled) - Bassett, Jennifer (Oxford, 2008)
This award-winning collection of adapted classic literature and original stories develops reading skills for low-beginning through advanced students.
Keywords: Reading comprehension,Short stories.,Truyện ngắn; Problems, exercises, etc